Occupants and energy performance: the Schrage House. (2nd January 2017) - Alonso, Carmen; La Roche, Pablo; Oteiza, Ignacio
ABSTRACT: An analysis of the energy performance of the Schrage House (Soriano, 1951) focuses on the user's role in the link between energy strategies and the effectiveness of user adaptation and control. A number of strategies were studied via energy simulation modelling based on documentary information, monitoring data and occupant interviews. The findings confirmed the importance of user awareness and active involvement in a home's passive behaviour as a regulator of the environment around the house and in the effectiveness of the strategies adopted. The strategies included insulation, controlling natural ventilation and infiltration, harnessing solar power and shading.